Supramolecular G4 Eutectogels of Guanosine with Solvent‐Induced Chiral Inversion and Excellent Electrochromic Activity - Gu, Chaonan; Peng, Yu; Li, Jingjing; Wang, Hai; Xie, Xiao‐Qiao; Cao, Xiaoyu; Liu, Chun‐Sen (Angewandte Chemie International Edition, 2020)
Supramolecular eutectogels, an emerging class of materials that have just developed very recently, offer a new opportunity for generating functional supramolecular gel materials in biocompatible anhydrous or low‐water media. As the first example of supramolecular G4 eutectogels, complexes of natural guanosine and H3BO3 exhibited excellent gelation capacity in choline chloride/alcohol deep eutectic solvents. The as‐prepared supramolecular eutectogels displayed unexpected solvent‐induced chiral inversion and significantly high ionic conductivity (up to 7.78 mS cm−1), as well as outstanding thixotropic/injectable properties, high thermal stability and excellent electrochromic activity. These features make these versatile supramolecular G4 eutectogels promising candidates for developing next‐generation flexible electronics with low environmental impact. Supramolecular eutectogels are an emerging class of materials that offer a new opportunity for generating functional gel materials in biocompatible anhydrous or low‐water media. Two guanosine‐based supramolecular G4 eutectogels with high ionic conductivity and solvent‐induced chiral inversion were developed that can be applied to fabricate a flexible electrochromic device.